FACTORS INFLUENCING CB-AIS QUALITY AND THEIR IMPACT ON USER SATISFACTION - Ai Teti Taryati; Yenni Carolina (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
Trise of information technology in the industrial revolution 4.0 impact on business processes. Business processes will be optimized by the support of the cloud as one of the alternatives. CB-AIS offers an innovative solution for companies, as it can increase efficiency, flexibility, accessibility, and the capacity to handle vast volumes of data. This study is based on TOE (Technology, Organization, Environment) approach and aims to investigate the elements that influence the quality of CB-AIS, such as security, top management support, and competitive pressure. Furthermore, this research investigates the effect of CB-AIS quality on user satisfaction. The sample includes employees from the banking sector in the Bandung area. PLS is used to analyze the data, facilitated by SmartPLS software. The results showed that competitive pressure, security, and top management support were significantly affected by CB-AIS. Moreover, the findings revealed that the quality of CB-AIS had a positive outcome on user satisfaction.